Hubungan Hak Asasi Manusia Dengan Konsep Ketatanegaraan - Triadi, Irwan; Priyantoro, Lucky; Lufthi, Al Daffa Naufal; Ikwanto, Mahia Albar; Pradana, David (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Human Rights (HAM) are rights that are inherent from the time humans are born and cannot be separated from humans at all, as well as a legal concept as well as a characteristic of a legal state which aspires and states that humans have rights related to themselves as individuals, and also is a deep and complex issue. So that the state is fully obliged to respect the citizenship status of its citizens, and prevent violations of human rights. The research method applied in this paper is the normative juridical method, namely legal research carried out by studying library materials or secondary data as a basis for analysis. This research was carried out by exploring the laws and regulations in force in Indonesia and literature related to the problems discussed in this paper. In a democratic society, human rights are considered a fundamental principle, which must be safeguarded and protected by the government. Meanwhile, state administration is a system of state regulation and administration based on law. The two are certainly interconnected and bound. Human Rights (HAM) in Indonesia are a very complex issue where every human being is attached to basic rights that have been destined since birth. This right must be respected, respected and protected by the state. Of all the challenges and hopes mentioned, human rights protection in the context of state administration in Indonesia has a fundamental role.